Effect of Modifying Intervention Set Size With Acquisition Rate Data While Practicing Single-Digit Multiplication Facts. (June 2016) - Burns, Matthew K.; Zaslofsky, Anne F.; Maki, Kathrin E.; Kwong, Elena
Incremental rehearsal (IR) has consistently led to effective retention of newly learned material, including math facts. The number of new items taught during one intervention session, called the intervention set, could be used to individualize the intervention. The appropriate amount of information that a student can rehearse and later recall during one intervention session is called the acquisition rate (AR). The current study taught single-digit multiplication facts with factors of 6, 7, and 8 to 55 third- and fourth-grade students. Each student was randomly assigned to be taught two multiplication math facts, eight multiplication math facts, or a set size determined by each student's AR. The average AR was 4.05 ( SD = 0.71). Set size led to a significant and large effect on retention, percentage of multiplication math facts retained, and efficiency as computed by math facts retained per minute of intervention time. IR appeared to be an effective intervention when AR data were used to determine the intervention set size, and it was more efficient to do so.